2013
DOI: 10.18357/ijcyfs41201311851
|View full text |Cite
|
Sign up to set email alerts
|

A Context of Domestic Violence: Learnings for Prevention From the Calgary Filipino Community

Abstract: Abstract:There is a lack of interpretive research in the domestic violence literature and, in particular, within an ethnocultural context. Interviews were held with four Filipina women in Calgary, Alberta who had previously been in violent relationships, in combination with a referral group of key informants with leadership and knowledge of community issues related to domestic violence. By adopting a phenomenological approach to the research, it was hoped that new understandings of what is identified in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Although the relationship between CM and IPV perpetration in women is obviously important, the possibility of intervening on CM to prevent male violence against their intimate partners is especially relevant, since male-initiated IPV is more common and potentially more dangerous. Wells et al (2013) have identified several promising areas for engaging men and boys in IPV prevention, including (1) engaging fathers as key participants in family strengthening and support, for example, through the development and enhancement of parental leave policies for men and the implementation of fatherhood support and training programs; (2) engaging key role models such as sport coaches and athletes to promote positive male relational behaviors and to influence men as bystanders, peer influencers, and mentors toward ending IPV (Minerson, Carolo, Dinner, & Jones, 2011); (3) providing men and boys with the skills and opportunity to speak up against sexism, inequity, and the maltreatment of women and girls (Flood, 2010); and (4) supporting minority community leaders in their implementation of appropriate responses to violence (Trevethan, Moore, & Allegri, 2005). Although such suggestions also apply to male victims of IPV, they typically have been focused on preventing violence against girls and women perpetrated by boys and males.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between CM and IPV perpetration in women is obviously important, the possibility of intervening on CM to prevent male violence against their intimate partners is especially relevant, since male-initiated IPV is more common and potentially more dangerous. Wells et al (2013) have identified several promising areas for engaging men and boys in IPV prevention, including (1) engaging fathers as key participants in family strengthening and support, for example, through the development and enhancement of parental leave policies for men and the implementation of fatherhood support and training programs; (2) engaging key role models such as sport coaches and athletes to promote positive male relational behaviors and to influence men as bystanders, peer influencers, and mentors toward ending IPV (Minerson, Carolo, Dinner, & Jones, 2011); (3) providing men and boys with the skills and opportunity to speak up against sexism, inequity, and the maltreatment of women and girls (Flood, 2010); and (4) supporting minority community leaders in their implementation of appropriate responses to violence (Trevethan, Moore, & Allegri, 2005). Although such suggestions also apply to male victims of IPV, they typically have been focused on preventing violence against girls and women perpetrated by boys and males.…”
Section: Discussionmentioning
confidence: 99%
“…The Philippines was colonized for a long time by foreign countries such as Spain, The United States and Japan, and several decades ago that resulted in the cultivation of Filipinos' colonial mentality and high regard for anything foreign (Alcuitas, Alcuitas-Imperial, Diocson, Ordinario, 1997;Wells et. al., 2013).…”
Section: Personal Barriers To Employmentmentioning
confidence: 99%
“…al., 2013). Filipino colonial mentality such as "west is the best," "America is a paradise" (Alcuitas, Alcuitas-Imperial, Diocson, Ordinario, 1997) and "Canada being a Graceland" (Wells et. al., 2013) contribute to Filipino immigrants' oppression in ways which are masqueraded as personal barriers to employment.…”
Section: Personal Barriers To Employmentmentioning
confidence: 99%
“…Migration can also empower women economically and increase their independence, improve their self-esteem and their general well-being (Raimundo, 2009). The fact is that even specific forms of forced migration of women, for example, migration resulting from conflict, can lead to modifications in existing gender roles and duties to women's benefit (Wells et al, 2013). Conversely, migration can also embed traditional roles and disparities and expose women to new vulnerabilities as the result of precarious legal status, exclusion and segregation (Adepoju, 2006).…”
Section: Introductionmentioning
confidence: 99%